Investigação dos efeitos estruturais de ligantes 1,3- diariltriazenidos simétricos orto-substituídos em complexos de mercúrio (II) - Silva, Angela (2007)
This work was accomplished with the interest in the synthesis of ortosubstituted ligands, with special prominence to the moiety __CF3, __Br and __NO2 and later the complexação with Hg(II). The first obtained result was the crystalline structure of the ligand (1), it crystallizes in the system crystalline monoclínico, space group Cc, with the given following crystallographic the a = 15,3122(12)Å, b = 4,8544(3)Å, c = 19,2804(15)Å, ß = 104,205(2)°, V = 1389,32(18)Å3, Z = 4, R1 = 0,0330 and wR2 = 0,0988. The molecular structure of the -ligand (1) it confirms the expected stereochemistry trans in relation to the doble bond in the diazoamine moiety. The interplanar angle [8,3(1)°] between the terminal phenyl rings indicate that the whole molecule is almost planar (r.m.s deviation = 0,0929 Å). The molecule shows intramolecular N__H...(F1,F2) bifurcated, and non-classical N__H...F hydrogen bonds. The unequal distribution of the double bond character among the N atoms of the diazoamine group, indicates a delocalization of the π electrons over the N=N__N(H) moiety towards the terminal 2-trifluormethylphenyl substituents. The subsequent results resulted in crystalline structures of compounds involving the ion Hg(II) (2), (3) and (4). The data in relation to the crystalline structures are gathered in the sequence, respectively: (2) it crystallizes in the system crystalline monoclinic, space group: C2/c, the a = 23,0736(5)Å, b = 107,82604(2)Å, c = 14,7387(3)Å, ß = 99,6590(10)°, V = 2623,70(10)Å3, Z = 4, R1 = 0,0232 and wR2 = 0,1187; (3) it crystallizes in the system crystalline monoclinic, space group C2/c, the a = 20,8663(6) Å, b = 9,9525(4) Å, c = 15,6013(5) Å, ß = 118,007(2)°, V = 2860,52(17) Å3, Z = 4, R1 = 0,0666 and wR2 = 0,1435 and the last obtained result is regarding the compound (4) it crystallizes in the system crystalline monoclinic, space group C2/C, The a = 22,5163(3) Å, b = 8,2234 (1)Å, c = 15,1037 (2) Å, β = 111,282(1), V = 2605,9(11), Z = 4, R1 = 0,078 e wR2 = 0,232. The compounds above mentioned present a behavior similar plenty crystallographic, because they are gathered in the same crystalline system and they are part of the same space group, however a particularity of each compond is detached in what refers to the electronic effects of the groups linked substituintes to the rings terminal phenila, that so much presents angles different interplanares as well as strong effect estérico in relation to Hg(II) shielding it of other ligands.